Severity of self-reported diseases and symptoms in Denmark - Avlund Kirsten; Rasmussen Niels; Iburg Kim (BMC, 2006)
Abstract Objective To estimate and rank the relative severity of self-reported diseases and symptoms in Denmark. Method The 1994 Danish Health and Morbidity Survey collected data from 5,472 Danes older than 16 years of age. Interviews (response frequency: 79%) gave information on diseases and symptoms; a self-administered SF-36 questionnaire (response frequency: 64%) provided information on health-related quality of life. The severity of diseases and symptoms was represented by the health-related quality of life scores that individuals suffering from particular diseases and symptoms obtained on the single dimensions of the SF-36 and on a combined sum of all dimensions. We applied logistic regression to control for the influence of sex, age and socio-economic status on the SF-36 score. We also analysed the interaction between socio-economic status and diseases on the SF-36 score. Results Females, more frequently than males, reported on all symptoms and all disease groups except injuries. People with relatively low levels of education reported most diseases, especially musculoskeletal and cardiovascular diseases, more frequently than people with higher education. Age-adjusted mean SF-36 scores for all dimensions combined showed that the symptoms of melancholy/depression and breathing difficulties, psychiatric disorders and respiratory diseases scored lowest (i.e. were most often associated with worse health). Females had lower SF-36 combined scores (worse health) than males on all symptoms. We found interaction between socio-economic status and respiratory diseases and musculoskeletal diseases on the SF-36 score. SF-36 scores also indicated significantly worse health among Danes with low education and income levels compared to those with higher education and income. Conclusion In 1994 the Danes most frequently reported musculoskeletal symptoms and diseases. Psychiatric disorders and respiratory diseases were identified as the most severe reported diseases. Due to the interaction between socio-economic status and some diseases, severity estimates should be interpreted with caution or stratified by socio-economic groups.